Marriage breakdown in Australia: social correlates, gender and initiator status - Hewitt, B (My University, 2008)
The report analyses retrospective data from all persons who were currently or had been previously married at Wave 1 of the Household, Income and Labour Dynamics in Australia (HILDA) survey (2001). The findings are grouped into three main themes: Social characteristics are important for understanding marriage breakdown. Women are more likely to initiate separation than men. Gender differences in the decision to separate or remain married.
Social Policy Research Paper Series
Keywords: Relationships; Relationships -- Dissolution; Families and relationships; Relationships; Dissolution; Families and relationships